Weak and Saturable Protein–Surfactant Interactions in the Denaturation of Apo-α-Lactalbumin by Acidic and Lactonic Sophorolipid - Andersen, Kell K.; Vad, Brian S.; Roelants, Sophie; van Bogaert, Inge N. A.; Otzen, Daniel E. (Frontiers in Microbiology, 2016)
Biosurfactants are of growing interest as sustainable alternatives to fossil-fuel-derived chemical surfactants, particularly for the detergent industry. To realize this potential, it is necessary to understand how they affect proteins which they may encounter in their applications. However knowledge of such interactions is limited. Here we present a study of the interactions between the model protein apo-alpha-lactalbumin and the biosurfactant sophorolipid (SL) produced by the yeast Starmerella bombicola. SL occurs both as an acidic and a lactonic form; the lactonic form (lactSL) is sparingly soluble and has a lower critical micelle concentration than the acidic form (acidSL). We show that acidSL affects apo-aLA in a similar way to the related glycolipid biosurfactant rhamnolipid (RL), with the important difference that RL is also active below the cmc in contrast to acidSL. Using isothermal titration calorimetry data, we show that acidSL has weak and saturable interactions with apo-aLA at low concentrations; due to the relatively low cmc of acidSL (which means that the monomer concentration is limited to ca. 0-1 mM SL), it is only possible to observe interactions with monomeric acidSL at high apo-aLA concentrations. However, the denaturation kinetics of apo-aLA in the presence of acidSL are consistent with a collaboration between monomeric and micellar surfactant species, similar to RL and nonionic or zwitterionic surfactants. Inclusion of lactSL as mixed micelles with acidSL lowers the cmc and this effectively reduces the rate of unfolding, emphasizing that SL like other biosurfactants is a gentle anionic surfactant. Our data highlight the potential of these biosurfactants for future use in the detergent industry.